2009
DOI: 10.1583/09-2711.1
|View full text |Cite
|
Sign up to set email alerts
|

Size of the Proximal Neck in AAAs Treated With Balloon-Expandable Stent-Grafts: CTA Findings in Mid- to Long-term Follow-up

Abstract: The study showed that the diameter reached at initial deployment did not increase further in the long term, which supports the safety and reliability of this modular balloon-expandable stent-graft and illustrates that this device does not produce dilatation of the proximal neck after deployment. Future dilatation of the aortic neck is unlikely, and consequently, migration or delayed type I endoleak are also unlikely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 47 publications
(74 reference statements)
2
13
0
1
Order By: Relevance
“…This study, like others before it4-11 demonstrated a high incidence of neck dilatation following EVAR with a self-expanding stent graft. We observed some degree of neck dilatation at the 4-year follow-up in all cases.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This study, like others before it4-11 demonstrated a high incidence of neck dilatation following EVAR with a self-expanding stent graft. We observed some degree of neck dilatation at the 4-year follow-up in all cases.…”
Section: Discussionsupporting
confidence: 86%
“…Several authors have described medium-term changes in aneurysm neck diameter after EVAR using a variety of stent grafts 4-11. These studies tended to treat neck dilatation as an all or nothing phenomenon, and focused on its incidence in varying assortments of device types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,24 Stent-graft migration and neck dilatation seem not to be problems for patients treated with balloon-expandable grafts. 25,26 Self-expanding stent-grafts, however, must be oversized to get enough radial force for proximal fixation. Balloon-expandable stent-grafts are dilated to the maximal diameter, so the Palmaz stent component will maintain its diameter without further force.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent comparative study by Savlovskis et al, repair with certain type of self-expandable stent (SES)—endografts (Nellix; Endologix, Irvine, CA, USA) caused progressive infrarenal aortic neck enlargement although repair with BES endografts did not cause any neck enlargement after a 24–34 months follow-up (34). Additionally, Peirano et al showed that the diameter reached at initial deployment did not increase further in the long term, which supports the safety and reliability of a modular BES graft and illustrates that this device does not produce dilatation of the proximal neck after deployment (35). However, data on BES grafts are heterogenous as most of the studies have used different types of BES grafts, and no concrete conclusions could be produced.…”
Section: Progression Of Proximal Aaa Neck After Evarmentioning
confidence: 91%